New Media and Women's Da'wah Movement in the New Normal Post Covid-19 Era - Athik Hidayatul Ummah (Postgraduate Program, Universitas Islam Negeri (UIN) K. H. Abdurrahman Wahid Pekalongan, Indonesia, 2021)
Internet and social media are source of information and religious knowledge references, especially for millennials and middle class urban communities. The transformation of Islamic da'wah from offline to online is still dominated by men preachers. Actually, women’s da’wah movement can be found in new media platforms but they get less attention. This study aims to explain the opportunities and challenges of women in Islamic da'wah in the digital era and the digital da'wah strategy of the Islamic Gender Justice studies (Ngaji KGI) community. The research method is virtual ethnography, a method to provide distinctive understanding of significance and implications of using new media. The perspective theory is innovation diffusion theory is the innovation of da'wah messages is communicated through various channels in social system. The results are new media provided a cyber space for equality, opportunity for women to appear in public and to show their scientific authority. The challenges in digital era are making creative da’wah messages to interest audience and ensuring that audience listens da'wah seriously, so that the goal of da'wah are achieved. The Ngaji KGI’s digital da'wah strategy can be accepted by audience because some factors are relative advantage, complexity, compatibility, triability, observability, and social media.